Research on the innovation efficiency evaluation of Unicorn Enterprises in Anhui Province based on the three-stage DEA model - Chu, Xueting; Zhu, Beibei; Gou, Xiaoyang (International Journal of Global Economics and Management, 2024)
Unicorns, as unlisted start-ups valued at more than $1 billion, have a significant impact on economic development and industry innovation. However, they also face problems such as unclear innovation paths and rigid business models, which can lead to lower user satisfaction and lower market value. The article begins with determining the importance of unicorns in the global economy, and points out that the efficiency of technological innovation transformation is the key to measuring their success. Then, the innovation efficiency of unicorn enterprises is evaluated through the three-stage DEA model, and 11 A-share unicorn concept listed companies in Anhui province are empiranalyzed. The research results show that different enterprises differ in the efficiency of scientific and technological innovation, and some enterprises such as COWA ROBOT and INNOTRON MEMORY performing well in pure technical efficiency and scale efficiency. Other companies need to further improve in technology application and scale management. In addition, the research also put forward countermeasures and suggestions such as promoting regional linkage and innovation resource sharing, optimizing government support policies and building an efficient scientific and technological innovation service system, so as to improve the transformation efficiency of scientific and technological innovation achievements of unicorn enterprises.